2007
DOI: 10.1038/sj.onc.1210975
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genomic aberration patterns are found in familial breast cancer associated with different immunohistochemical subtypes

Abstract: Five breast cancer subtypes have been described in sporadic breast cancer (SBC) using expression arrays: basal-like, ERBB2, normal breast-like, luminal A and B. These molecular subtypes show different genomic aberration patterns (GAPs). Recently, our group described these breast cancer subtypes in 50 non-BRCA1/2 familial tumors using immunohistochemistry assays. We extended this study to the other classes of familial breast cancer (FBC), including 62 tumors (18 BRCA1, 16 BRCA2 and 28 non-BRCA1/2), with the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
53
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 41 publications
12
53
2
1
Order By: Relevance
“…Furthermore, tumors of PALB2 carriers, similar to BRCA1, associate very strongly with the triple-negative (estrogen receptor/progesterone receptor/HER2 negative) and basal-like phenotype. This is not shared by tumors of BRCA2 carriers that correlate strongly with the luminalA subtype, as has also previously been suggested in a gene expression study (40), although also luminalB subtype has been found among BRCA2 tumors (41). In previous studies, only few PALB2 mutation carrier tumors have been studied, mainly for the estrogen receptor, progesterone receptor, or HER2 status, with inconsistent results (11 -15).…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, tumors of PALB2 carriers, similar to BRCA1, associate very strongly with the triple-negative (estrogen receptor/progesterone receptor/HER2 negative) and basal-like phenotype. This is not shared by tumors of BRCA2 carriers that correlate strongly with the luminalA subtype, as has also previously been suggested in a gene expression study (40), although also luminalB subtype has been found among BRCA2 tumors (41). In previous studies, only few PALB2 mutation carrier tumors have been studied, mainly for the estrogen receptor, progesterone receptor, or HER2 status, with inconsistent results (11 -15).…”
Section: Discussionsupporting
confidence: 54%
“…[90][91][92][93][94] This may be in part due to the presence of a dysfunctional BRCA1 pathway in these tumors. 32,82,83 BRCA1 gene promoter is methylated in 460% of medullary 95,96 and metaplastic 32 breast cancers of basal-like phenotype.…”
Section: S Badve Et Almentioning
confidence: 99%
“…S1), with p53 mutations, and with the basal-like phenotype (Fig. S2), a class of breast cancer that has greater chromosomal copy number variation and genetic complexity than other subtypes of breast cancer (19)(20)(21).…”
Section: High Levels Of Mps1 Correlate With High Histologic Grade In mentioning
confidence: 99%